2019
DOI: 10.1257/pol.20170570
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Run Effects of Teacher Collective Bargaining

Abstract: We analyze how exposure to teacher collective bargaining affects long-run outcomes for students, exploiting the timing of state dutyto-bargain law passage in a cross-cohort difference-in-difference framework. Among men, exposure to a duty-to-bargain law in the first 10 years after passage depresses annual earnings by $2,134 (3.93 percent), decreases weekly hours worked by 0.42, and reduces employment and labor force participation. The earnings estimate implies that current duty-to-bargain laws reduce earnings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Moe (2009), Marianno and Strunk (2018), and Strunk and McEachin (2011) found that more restrictive collective bargaining agreements were associated with null to negative effects on student outcomes in California. More recently, Baron (2018) found evidence from Wisconsin's Act 10 to suggest that teachers' unions reduced average test scores by 20 percent, and Lovenheim and Willén (2019) found that exposure to duty-to-bargain laws reduced annual earnings by 3.93 percent and hours worked per week by 0.42 for men. However, Matsudaira and Patterson (2017) found that teacher unionization in California charter schools increased math achievement by 17 percent but had no effects on reading achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moe (2009), Marianno and Strunk (2018), and Strunk and McEachin (2011) found that more restrictive collective bargaining agreements were associated with null to negative effects on student outcomes in California. More recently, Baron (2018) found evidence from Wisconsin's Act 10 to suggest that teachers' unions reduced average test scores by 20 percent, and Lovenheim and Willén (2019) found that exposure to duty-to-bargain laws reduced annual earnings by 3.93 percent and hours worked per week by 0.42 for men. However, Matsudaira and Patterson (2017) found that teacher unionization in California charter schools increased math achievement by 17 percent but had no effects on reading achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoxby (1996) and Lovenheim (2009) showed that union effects on student outcome, measured by high school dropout rate, are either negative or insignificant. Lovenheim and Willen (2019) examined more long‐run effects of unions and found that students educated under duty‐to‐bargain laws had lower annual incomes later in life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…32 Some studies, however, find evidence of negative effects of teachers' unions on student outcomes (e.g. Hoxby 1996;Lott and Kenny 2013;Lovenheim and Willen 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2 The evidence on teachers' unions generally shows increases in intermediate inputs such as teacher salaries (e.g. Hoxby 1996;West and Mykerezi 2011;Brunner and Squires 2013), while results are more mixed for student outcomes (Hoxby, 1996;Lovenheim, 2009;Lott and Kenny, 2013;Lovenheim and Willen, 2016). See Cowen and Strunk (2015) for a recent survey of this literature.…”
Section: Introductionmentioning
confidence: 99%